Public service ethics in Nigeria’s local government system (2003)
This paper attempts to explain the ethical crisis in local government in Nigeria by' examining the structural and nonnative ethical content of local government reforms. It argued that, although efforts were made to integrate public service ethics into the reforms, ethics programmes were unsystematic and were for a long time very limited. Moreover, key actors did not demonstrate serious commitment to them. The reason for the lack of commitment is attributed to the instrumental use of corruption for regime sustenance that shot through Nigeria's politics of distributive federalism, which came to its own in the last two decades. This has destroyed the idea of public service and generated strong forces within local government angling for a share of the "national cake." Popular accountability has been undermined by the disjunction of the location of expenditure from the sources of local government revenue.